Perception and adaptation to climate change in vulnerable regions - A. Jiménez Bedoya; F. Fuentes Gandara; R. Paternina Uribe; J. Pinedo Hernández (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Climate change perception and adaptation options is crucial to sustaining livelihood and well-being humanity. In Colombia, interest in climate change is increasing, reflected in growing attention towards adaptation and mitigation strategies. Specific research on this topic is scarce, particularly in ecologically valuable areas like the La Mojana region. The objective of this study was to evaluate the perception of different focus population groups such as fishermen, farmers and ranchers on climate change, regional adaptation strategies and implementation of public policies in the La Mojana Region of Northern Colombia, which is highly vulnerable to extreme climate phenomena. The dynamics of national and global scientific production were evaluated through bibliometric analysis of perception and adaptation policies to climate change.METHODS: Primary data was collected through semi-structured questionnaire interviews involving 420 participants from the fishing, agriculture, and livestock sectors to understand their perceptions of climate change risks and the adaptation strategies they have adopted. A bibliometric analysis using the SCOPUS scientific database was conducted to explore global and Latin American publication trends related to climate change perception and adaptation policies, with a particular focus on Colombia. This analysis highlights current research directions and academic impacts in climate change, public policies, and adaptation strategies.FINDINGS: The results showed that 100 percent of respondents perceived climate change over the last 20 years, particularly in rain-drought and sowing-harvest cycles, previously predictable. Focus groups' perception aligned with historical meteorological data on flood and La Niña phenomena. Priorities for government intervention include response to early emergencies, community participation, and stakeholder collaboration in future planning. Adaptation strategies included community management, ecosystem conservation, resilient housing and livestock, sustainable water management, and crop diversification. Colombia ranks third in Latin America for scientific production on climate change perception and adaptation policies, with political context and international compliance key factors.CONCLUSION: The study highlights how climate change affects psychological well-being through social and economic insecurity, exacerbated by the local government's lack of intervention to mitigate the vulnerability of focal groups and strengthen their adaptation and resilience capacities against climate change. It also underscores Colombia's significant role in regional scientific production on climate change perception, emphasizing the urgent need for more research to delve into these issues and enhance adaptation strategies in the region.